Design of a Website-Based Climbing Equipment Registration and Rental Information System Using the Waterfall Method - Efendi, Tessa Inriani; Harlinda L; Amaliah Faradibah (Yayasan Kita Menulis, 2026)
This research was motivated by the manual registration and equipment rental process at Lembah Lohe, Gowa Regency, which led to data recording errors, data loss risks, and low administrative efficiency. The objective of this study was to design a web-based hiking registration and equipment rental information system to improve data management effectiveness. The research applied the Waterfall method consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using PHP and MySQL and tested using Black Box Testing (Alpha and Beta). The results showed that all system functions operated according to specifications, and Beta testing produced an average index score of 82.40%, categorized as Very Good. Therefore, the developed system improves efficiency, accuracy, and accessibility of information for both hikers and administrators.